PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT (Studi Pelayanan Badan Penanggulangan Bencana Daerah Kabupaten Kaur Saat Banjir Di Desa Tanjung Besar dan Desa Selasih) - Fitriana, Endang (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
This research was conducted in Tanjung Besar Village and Selasih Village, Kaur Regency. Tanjung Besar Village and Selasih Village are the two villages that most often experience flood disasters. The aim of this research is to determine the effect of service quality on community satisfaction with the services provided by the Kaur Regional Disaster Management Agency during floods in Kaur district. This research is a quantitative study of forty respondents who experienced flood disasters. Based on the results of management studies, it is known that service quality is guaranteed by: Honesty, responsiveness, commitment, empathy and sadness on one part, at the same time followed by an impact that is good and important for life. public. Based on the results of the t test and F test, the fifth result shows that the t value is less than 0.05 and the significance of the F value is less than 0.05. This confirms our previous hypothesis.